In Vivo Ultra-Fast Photoacoustic Flow Cytometry of Circulating Human Melanoma Cells Using Near-Ingrared High-Pulse Rate Lasers - Nedosekin, Dmitry A. (2011)
The circulating tumor cells (CTCs) appear to be a marker of metastasis development, especially, for highly aggressive and epidemically growing melanoma malignancy that is often metastatic at early stages. Recently, we introduced in vivo photoacoustic (PA) flow cytometry (PAFC) for label-free detection of mouse B16F10 CTCs in melanoma-bearing mice using melanin as an intrinsic marker. Here, we significantly improve the speed of PAFC by using a high pulse repetition rate laser operating at 820 and 1064 nm wavelengths. This platform was used in preclinical studies for label-free PA detection of low pigmented human CTCs. Demonstrated label-free PAFC detection, low level of background signals, and favorable safety standards for near infrared irradiation suggest that a fiber laser operating at 1064 nm at pulse repetition rates up to 0.5 MHz could be a promising source for portable clinical PAFC devices. The possible applications can include early diagnosis of melanoma at the parallel progression of primary tumor and CTCs, detection of cancer recurrence, residual disease, and real-time monitoring of therapy efficiency by counting CTCs before, during and after therapeutic intervention. Herewith, we also address sensitivity of label-free PAFC melanoma CTCs detection and introduce in vivo CTCs targeting by magnetic nanoparticles conjugated with specific antibody and magnetic cells enrichment.